Ionic Liquid-Incorporated Metal-Organic Framework with High Magnesium Ion Conductivity for Quasi-Solid-State Magnesium Batteries - Wei, Zhixuan; Maile, Ruben; Riegger, Luise M.; Rohnke, Marcus; Müller-Buschbaum, Klaus; Janek, Jürgen; Justus Liebig University Giessen (My University, 2022)
Magnesium batteries are promising candidates for post-lithium energy storage systems due to their low cost, high volumetric energy density, and low risk of dendrite formation. This study reports a new magnesium ion conducting ionogel electrolyte based on a Metal-Organic Framework (MOF) structure (UiO-66) impregnated with an ionic liquid, magnesium bis[(trifluoromethyl)sulfonyl]imide in 1-ethyl-3-methylimidazolium bis[(trifluoromethyl)sulfonyl]imide. Comparably high conductivity of 5.7×10−5 S cm−1 can be achieved at room temperature. By employing the prepared MOF-ionogel electrolyte, a reversible quasi-solid-state magnesium battery (QSSMB) is reported. Surface analysis unveils the possible origin of the large overpotential of magnesium plating and stripping. The findings suggest that MOF-based materials are a promising class of ionogel electrolyte templates for QSSMBs. The results on the magnesium anode will be useful to define optimization strategies for magnesium metal anodes in SSMBs.
Keywords: interface; ionic liquids; ionogel electrolyte; magnesium battery; metal-organic frameworks; ddc:540